2021
DOI: 10.1186/s13039-021-00562-1
|View full text |Cite
|
Sign up to set email alerts
|

A new case of 17p13.3p13.1 microduplication resulted from unbalanced translocation: clinical and molecular cytogenetic characterization

Abstract: Copy number gain 17 p13.3p13.1 was detected by chromosomal microarray (CMA) in a girl with developmental/speech delay and facial dysmorphism. FISH studies made it possible to establish that the identified genomic imbalance is the unbalanced t(9;17) translocation of maternal origin. Clinical features of the patient are also discussed. The advisability of using the combination of CMA and FISH analysis is shown. Copy number gains detected by clinical CMA should be confirmed using FISH analysis in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The application of highresolution molecular cytogenetic methods, particularly FISH and CMA, are becoming indispensable to detect cryptic imbalances inside or outside of the breakpoint regions. Moreover, Markova et al (2021) concluded that CMA allowed identifying the unbalanced fragment responsible for occurrence of clinical features in the patient. However, it is impossible to determine a structure of derivative chromosomes using the array data alone.…”
Section: Discussionmentioning
confidence: 99%
“…The application of highresolution molecular cytogenetic methods, particularly FISH and CMA, are becoming indispensable to detect cryptic imbalances inside or outside of the breakpoint regions. Moreover, Markova et al (2021) concluded that CMA allowed identifying the unbalanced fragment responsible for occurrence of clinical features in the patient. However, it is impossible to determine a structure of derivative chromosomes using the array data alone.…”
Section: Discussionmentioning
confidence: 99%